The Effect of Mind Mapping Media on Student Learning Outcomes - Ridwan, Muhammad; Mahaputra, M. Ridho; Maharani, Amalina (Siber International Journal of Education Technology (SIJET), 2023)
This study aims to see the effect of use Mind Map Media (Mind Mapping) on student learning outcomes in social studies class IX at SMP Negeri 1 Lubuk Attitude. This research uses a quantitative approach in the form of Quasy Experiment . The technique used in sampling was purposive sampling , so that the samples were students of class IX.6 (Experimental class ) and students of class IX . 4 (Control class). Data collection techniques in the form of objective questions as many as 30 questions. After obtaining the data, a normality test and homogeneity test were carried out on the learning outcome data, then the t-test was continued . The results of the study show the average value of students who use Mind Map Media (Mind Mapping) that is 77.53 higher than students who use conventional media that is 70.5.